Return of the lysergamides. Part III: Analytical characterization of N6‐ethyl‐6‐norlysergic acid diethylamide (ETH‐LAD) and 1‐propionyl ETH‐LAD (1P–ETH‐LAD). Issue 10 (10th May 2017) - Brandt, Simon D.; Kavanagh, Pierce V.; Westphal, Folker; Elliott, Simon P.; Wallach, Jason; Stratford, Alexander; Nichols, David E.; Halberstadt, Adam L.
Abstract : The psychoactive properties of lysergic acid diethylamide (LSD) have fascinated scientists across disciplines and the exploration of other analogues and derivatives has been motivated by deepening the understanding of ligand‐receptor interactions at the molecular level as well as by the search for new therapeutics. Several LSD congeners have appeared on the new psychoactive substances (NPS) market in the form of blotters or powders. Examples include 1‐propionyl‐LSD (1P–LSD), AL‐LAD, and LSZ. The absence of analytical data for novel compounds is a frequent challenge encountered in clinical and toxicological investigations. Two newly emerging lysergamides, namely N 6 ‐ethyl‐6‐norlysergic acid diethylamide (ETH‐LAD) and 1P–ETH‐LAD, were characterized by gas chromatography–mass spectrometry (GC–MS), low and high mass accuracy electrospray MS(/MS), GC solid‐state infrared analysis, high performance liquid chromatography diode array detection as well as nuclear magnetic resonance spectroscopy. Limited analytical data for ETH‐LAD were previously available, whereas information about 1P–ETH‐LAD has not previously been encountered in the scientific literature. This study extends the characterization of lysergamides distributed on the NPS market, which will help to make analytical data available to clinicians, toxicologists, and other stakeholders who are likely to encounter these substances. The analysis of a test incubation of 1P–ETH‐LAD with human serum at 37°C by LC single quadrupole MS at various time points (0–6 h, once per hour and one measurement after 24 h) revealed the formation of ETH‐LAD, suggesting that 1P–ETH‐LAD might serve as a pro‐drug. 1P–ETH‐LAD was still detectable in serum after 24 h. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : N 6 ‐Ethyl‐6‐norlysergic acid diethylamide (ETH‐LAD) and 1‐propionyl‐ETH‐LAD, two newly emerging psychoactive lysergamides, were subjected to extensive analytical characterization. A test incubation of 1P–ETH‐LAD with human serum at 37°C resulted in the formation of ETH‐LAD, suggesting that 1P–ETH‐LAD might serve as a pro‐drug in vivo .